Shift work amongst older UK workers and job exit. (25th October 2021) - Bevilacqua, G; D'Angelo, S; Ntani, G; Stevens, M; Linaker, C H; Walker-Bone, K
Abstract: Background: Night/shift work may be increasing but there are few data about the prevalence amongst older workers. With governments encouraging people to work to older ages, it is important to know how feasible night/shift work is for them and whether there are any adverse health consequences. Aims: Amongst current older workers (aged 50–64 years), to explore the prevalence of night/shift working and evaluate its health impacts and sustainability over 4 years of follow-up. Methods: Data from the Health and Employment After Fifty cohort were used to describe the demographic, job and health characteristics of men and women undertaking night/shift work. Longitudinal data were used to examine the number and nature of exits annually thereafter. Results: Amongst the 5409 working at baseline, 32% reported night/shift work in sectors which differed by sex. Night/shift workers were more likely to be: current smokers; doing physically demanding work; struggling to cope at work; dissatisfied with their hours; depressed; sleeping poorly; rating their health poorly. Women whose job involves night work were more likely to exit the workforce over 4 years. Conclusions: Almost one in three contemporary UK older workers report night/shift work. We found some evidence of adverse impacts on health, sleep and well-being and higher rates of job exit amongst women. More research is needed but night/shift work may be challenging to sustain for older workers and could have health consequences.